초음파 뼈흡인기를 이용한 코경유 눈물주머니코안연결술 - 이수정(Soo Jung Lee), 김중엽(Jung Yup Kim), 권재환(Jae Hwan Kwon) (Daihan angwa haghoi jabji, 2015)
목적: 초음파 뼈흡인기를 이용한 코경유 눈물주머니코안연결술의 결과를 보고하고자 한다. 대상과 방법: 2014년 1월부터 2014년 6월까지 코눈물관폐쇄 환자 12명 15안을 대상으로 코경유 눈물주머니코안연결술 시행 시 초음파뼈흡인기(Cusa, Integra, New Jersey, NJ, USA)를 이용하여 누공을 만들었다. 결과: 모든 안에서 눈물 흘림의 완전한 개선을 보였고 합병증은 관찰되지 않았으며 수술 후 10개월 이상의 경과관찰 중 재발 소견은보이지 않고 있다. 결론: 국내에서 처음으로 초음파 뼈흡인기를 사용하여 코경유 눈물주머니코안연결술을 시행하여 좋은 결과를 얻었으며, 초음파 뼈흡인기를 사용한 수술법은 열손상과 연부조직 손상이 적고 빠른 시간 내에 정확한 골공을 형성할 수 있어 드릴 및 론저를 사용하는방법을 대체할 수 있는 유용한 방법이라고 생각된다. Purpose: To report the results of 15 endoscopic dacryocystorhinostomy (eDCR) cases using ultrasonic bone aspirator (UBA) and evaluate the UBA efficiency in these surgeries. Methods: Fifteen eyes of 12 patients presenting with nasolacrimal duct obstruction were evaluated in the present study. eDCR and osteotomy were performed using UBA (Cusa excel, Integra, New Jersey, NJ, USA) from January 2014 to June 2014. Results: All the patients showed complete resolution of the epiphora. There were no complications or recurrences for a minimum of 10 months postoperatively. Conclusions: This is the first report on eDCR using UBA. The surgeries were successful and no complications were observed. eDCR using UBA is an easy, safe and effective technique with minimal heat production, minimal damage to the surrounding soft tissue and quick and precise bone removal. KCI Citation Count: 0